Eosinophilic cystitis: treatment with intravesical steroids and oral antihistamines. (6th September 2013) - Zaman, Shahriar Raj; Vermeulen, Tersia L; Parry, Jeremy
Abstract : This is a case of eosinophilic cystitis in a 56-year-old indigenous Australian woman who presented with urosepsis on the background of a urinary tract infection unresponsive to oral antibiotics. After resolution of the urosepsis, she had persisting urinary retention and a cystoscopy/bladder biopsy suggested eosinophilic cystitis. After 1 month of intravesical hydrocortisone and oral loratadine, repeat cystoscopy showed vast improvement in the bladder lesions. This case further strengthens the use of intravesical steroids and oral antihistamines for the management of eosinophilic cystitis.